Exercise Tolerance in Patients With Idiopathic Pulmonary Fibrosis, Effect of Supplemental Oxy-Gen - Chlumský, J; Stehlík, L; Šterclová, M; Smetanová, J; Zindr, O (Physiological research, 2022)
Exercise tolerance in patients with idiopathic pulmonary fibrosis IPF is mainly limited by mechanical constrain of ventilation and high physiologic dead space. Oxygen enriched gas inhalation seems to increase ventilatory efficiency by reduction of dead space to tidal volume ratio (VD/VT) which probably mirrors improved pulmonary capillary flow and leads to longer physical tolerance at lower level of minute ventilation. The effect is noticeable at FIO2 that can be delivered in rehabilitation purposes or daily living activities.
Keywords: dechový objem; mrtvý prostor dýchacích cest; zátěžový test; Oxygen; tolerance zátěže; kyslík; Exercise Tolerance; Lung; Humans; Idiopathic Pulmonary Fibrosis; Tidal Volume; Respiratory Dead Space; lidé; Exercise Test; idiopatická plicní fibróza; plíce